2021
DOI: 10.1088/1742-6596/1882/1/012051
|View full text |Cite
|
Sign up to set email alerts
|

Efforts to improve students’ mathematical critical thinking ability by using Team Assisted Individualization learning model

Abstract: The development of critical thinking is the goal of the Indonesian education curriculum. However, research on how to develop and improve these abilities is still rarely studied. In this article, we offer a team assisted individualization-learning model in improving critical thinking skills. The objectives of this study were (1) to describe the improvement of students’ mathematical-critical thinking skills using the Team Assisted Individualization learning model, (2) To determine the increase in students’ criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Tauran [50] also applied the Team Assisted Individualization learning model to improve high school students' "reasoning" ability, which is an important aspect of problem-solving ability. Furthermore, Marasabessy, et al [51], in a study involving fourth-semester students in a mathematics education study program, found a significant increase in students' mathematical critical thinking skills after applying the Team Assisted Individualization type cooperative learning model.…”
Section: Team-assisted Individualization Learning Model Affects the P...mentioning
confidence: 99%
“…Tauran [50] also applied the Team Assisted Individualization learning model to improve high school students' "reasoning" ability, which is an important aspect of problem-solving ability. Furthermore, Marasabessy, et al [51], in a study involving fourth-semester students in a mathematics education study program, found a significant increase in students' mathematical critical thinking skills after applying the Team Assisted Individualization type cooperative learning model.…”
Section: Team-assisted Individualization Learning Model Affects the P...mentioning
confidence: 99%
“…In Indonesia, there are also many studies on critical thinking skills, especially in the context of mathematics education. several studies have focused on the distribution of students' critical thinking levels (Bayuningsih et al, 2018;Ghadi et al, 2015;Sahin et al, 2016), and other studies that discuss the effect of special learning designs on students' critical thinking abilities (Agustina et al, 2020;Marasabessy et al, 2021;Solodikhina & Solodikhina, 2019). There is also research that discusses the relationship between critical thinking skills and other parameters of student achievement (Palinussa, 2013).…”
mentioning
confidence: 99%